GERAKAN ORANGTUA MEMBACAKAN BUKU DALAM MENUMBUHKAN MINAT BACA SEJAK USIA DINI DI PAUD AL-JAMIL - Arianti, Fiska (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The role of the family is very important to improve the literacy of children, because the family is the smallest unit in the community and is the first learning environment for children. The national movement of parents reading books to children (GERNAS BAKU) is a movement to support the role of families to foster interest in reading children through habituation at home, in early childhood or in the community. PAUD Al-Jamil is one of the early childhood institutions located in Banyuasin district that seeks to promote this GERNAS BAKU program so that children of early age will grow their interest and love to read. The activities conducted at PAUD Al-Jamil Institute for GERNAS BAKU are ( 1) to socialize what is GERNAS BAKU. (2) Parenting Activity with Theme How to Grow Children's Reading Interest